PENDIDIKAN HUMANIS DALAM HADITS NABI TERHADAP PRAKTIK TARBAWI RASULULLAH DALAM SHAHIH AL-BUKHARI - Nabila Al Najla; Ainul Gani; Muhammad Akmansyah; Amirudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the humanistic education model reflected in the prophetic traditions (hadith) of the Prophet Muhammad as documented in Sahih al-Bukhari, with a critical focus on the educational (tarbawi) practices of the Prophet. The research is grounded in the problem of the limited exploration of humanistic values within classical hadith sources, despite their significant relevance to contemporary educational challenges. The aim of this study is to identify, analyze, and conceptualize the principles of humanistic education embedded in the Prophet’s pedagogical approaches. This research employs a qualitative library-based methodology, utilizing hadith texts from Sahih al-Bukhari as primary sources and supported by relevant scholarly literature. Data were analyzed using descriptive-analytical and critical approaches to uncover patterns of educational interaction that emphasize dignity, compassion, justice, inclusivity, and respect for individual differences. The findings reveal that the Prophet’s educational practices demonstrate a strong humanistic orientation, characterized by dialogical communication, empathy toward learners, contextual understanding, and moral persuasion rather than coercion. These practices reflect a holistic educational model that integrates cognitive, affective, and ethical dimensions. The study concludes that the humanistic education model derived from prophetic traditions offers a valuable conceptual framework for developing Islamic education that is humane, inclusive, and responsive to contemporary educational needs.